International Scientific Conference "Socio-Political and Religious Ideas and Movements in the 20th-21st Centuries", Latvia, Riga, 4-5 October 2018 : Abstracts - (:unkn) unknown (LU Filozofijas un socioloģijas institūts, 2018)
The conference facilitated the exchange of ideas and the results of the latest studies on the reciprocity and significance of religious and socially political ideas (ideologies) in contemporary society. In the modern-day ever-changing political situation, an increasing danger to the safety and stability of society is caused by the manipulations of the seemingly traditional conceptions of ethical, religious and cultural values evident in the public discourse and media space. Under the impact of global processes, social anxiety and ethical disorientation facilitate a dangerous trend to trust the populist ideologies and quasi-religious ideas, as well as increase the level of radicalisation of religious communities. In order to understand the current processes, it is necessary to examine the 20 th century experience, especially in the so-called “socialist bloc” countries, where the secularisation processes of society took place under the circumstances of authoritarian / totalitarian regime, facilitating not only deeply rooted political and social myths in society, but also their cultivation in the educational system, media space and politics. Looking from a modern-day perspective, it is important to establish a multidimensional understanding of the connection between socially political ideas and the religious consciousness in society, as well as in the experience of social groups and individuals. For the interpretation and analysis of the current situation it is necessary to develop a retrospective perspective on the processes in the 20 th century. Participants of the conference discussed on such topics: - The reciprocity of socio-political ideologies and religious movements in the post-secular society; - The reciprocity of anarchistic and religious ideas in the 20 th – 21 st centuries; - Political and religious movements in the USSR (Bolshevism and the reaction of the Church towards it; the atheist ideology and the problems of religiosity preservation; the dissident movement and the Church; non-traditional religious groups in the circumstances of the Soviet regime); - Political and religious movements in Latin America (Communism and liberation theology); - Religion and the role of religious institutions in global peace processes in the 20 th – 21 st centuries; - Religion and conflicts on a global scale in the 20 th – 21 st centuries; -The potential of religious groups in the politically social sphere: the current tendencies and problems in the Baltic States and the EU.
Keywords: Atheism; Liberation theology; islam; Russian Orthodox Church; Stalinism; secularization; Post-Soviet States; religious tourism; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology::History of religion; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology::Church studies; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects